1985
DOI: 10.1111/j.1365-2923.1985.tb01314.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, validity and efficiency of multiple choice question and patient management problem item formats in assessment of clinical competence

Abstract: Despite a lack of face validity, there continues to be heavy reliance on objective paper-and-pencil measures of clinical competence. Among these measures, the most common item formats are patient management problems (PMPs) and three types of multiple choice questions (MCQs): one-best-answer (A-types); matching questions (M-types); and multiple true/false questions (X-types). The purpose of this study is to compare the reliability, validity and efficiency of these item formats with particular focus on whether M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
7

Year Published

1995
1995
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 9 publications
3
40
0
7
Order By: Relevance
“…[10][11][12][13][14][15] The first session focused on formulating clinical questions using the patient, intervention, comparison, outcome method. 15 17 and have been shown to correlate with assessment by unannounced standardized patients, an accepted "gold standard." 18 We selected 15 multiple-choice questions based on clinical vignettes from the Medical Knowledge Self-Assessment Program questions CD.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12][13][14][15] The first session focused on formulating clinical questions using the patient, intervention, comparison, outcome method. 15 17 and have been shown to correlate with assessment by unannounced standardized patients, an accepted "gold standard." 18 We selected 15 multiple-choice questions based on clinical vignettes from the Medical Knowledge Self-Assessment Program questions CD.…”
Section: Methodsmentioning
confidence: 99%
“…Classified as high [9], [11]A minimum of 40 high-quality questions are needed to yield α Cronbach’s α of 0.8 [6]. …”
Section: Discussionmentioning
confidence: 99%
“…However, few studies of criterion-related validity have been reported (Albanese, Kent, & Whitney, 1979;Norcini, Swanson, Grosso, & Webster, 1985). Further, most of this research has used data from elementary, secondary, and undergraduate students; few studies have been reported using postgraduate professional examination data.…”
Section: American Board Of Internal Medicinementioning
confidence: 89%